2022
DOI: 10.1007/s11657-022-01110-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective observational study of osteoporosis management after a fragility fracture in primary care

Abstract: Summary In many countries, osteoporosis is predominantly managed by primary care physicians; however, management after a fragility fracture has not been widely investigated. We describe osteoporosis care gaps in a real-world patient cohort. Our findings help inform initiatives to identify and overcome obstacles to effective management of patients after fragility fracture. Purpose A fragility fracture is a major risk factor for subsequent fracture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Primary care physicians and/or specialists in osteoporosis should be involved in the follow-up of patients with VFF in the acute and chronic phases when treated with bisphosphonates or denosumab, whereas a geriatrician should be responsible for the follow-up of frail or disabled subjects. However, despite achieving 100% agreement on the role of primary care physicians in the management of fragility fractures in older people, it has been shown that the diagnosis and treatment of osteoporosis, as well as fracture risk assessment, is frequently lacking in the primary care setting [ 46 , 47 ]. Therefore, effective communication with primary care professionals (e-consultation or other resources of telemedicine) is a critical aspect of the appropriate interdisciplinary management of older patients with VFF.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians and/or specialists in osteoporosis should be involved in the follow-up of patients with VFF in the acute and chronic phases when treated with bisphosphonates or denosumab, whereas a geriatrician should be responsible for the follow-up of frail or disabled subjects. However, despite achieving 100% agreement on the role of primary care physicians in the management of fragility fractures in older people, it has been shown that the diagnosis and treatment of osteoporosis, as well as fracture risk assessment, is frequently lacking in the primary care setting [ 46 , 47 ]. Therefore, effective communication with primary care professionals (e-consultation or other resources of telemedicine) is a critical aspect of the appropriate interdisciplinary management of older patients with VFF.…”
Section: Discussionmentioning
confidence: 99%
“…6 Many interventions aimed at identifying and improving fragility fracture prevention in routine primary care settings have had little impact. 18–20 Therefore, novel interventions are needed in clinical settings that deliver acute ambulatory healthcare services, such as the Emergency Department (ED).…”
mentioning
confidence: 99%